Workload and Stress Incidents Among Production Workers at PT. X, Bekasi, West Java, 2025 - Indah Restiaty; Muslim, Burhan; Rojali, Rojali; Masyeni, Suci Ratu; Permatasari, Bina Rachma (Jurnal Ar Ro'is Mandalika (Armada), 2025)
An imbalance between workload and individual capacity may lead to work stress, which negatively impacts both employees’ health and company productivity. This study aims to analyze the relationship between workload and work stress among production workers at PT. X, Bekasi, West Java, in 2025. A quantitative method with an analytic cross-sectional design was applied. A total of 35 permanent production workers were selected using purposive sampling, and data were collected through questionnaires measuring workload indicators (metabolic rate and physical workload at the workplace) and work stress indicators (role ambiguity, role conflict, quantitative workload, qualitative workload, and career development). Data were analyzed using the Chi-Square test. The results showed that most workers experienced light workload, while work stress was mostly in the mild to moderate categories. The Chi-Square test produced a p-value of 0.014, indicating a significant relationship between workload and work stress. These findings highlight the importance of proper workload management, including task arrangement, job rotation, and career development strategies to reduce the risk of work stress and maintain productivity among production workers.